STUDENT’S PERCEPTION TOWARD PERSONAL CHARACTERISTICS OF GOOD ENGLISH TEACHERS IN VOCATIONAL HIGH SCHOOL (SMK) - darussalam, ahmad (Humanitatis : Journal of Language and Literature, 2019)
This study conducted under the basic assumption that the teacher is one of the critical factors determining the success of teaching and learning. A teacher is the fruitful source of information, knowledge, and science to the students. This role would never lose from the personal characteristics of the teacher’s self as human being. The good characteristics of teachers usually make conductive situation for students in learning The purpose of this study was to find and identify the characteristics of English teachers. The subjects of this study were taken from the student’s of SMK Negeri 1Tanah Grogot with total number of respondents was 122 students. The procedure included: giving a questionaire to the students of the third class of SMK Negeri 1 Tanah Grogot and asking them to the select their good English teachers and the characteristics of the teachers, then the researcher interviewed the teachers to ask them question about the qualities they had based on questionaire of student’s perception. The researcher observed in the classroom when the teachers were teaching. The data analyzed descriptively. The result showed that all of the good English teacher had many similar characteristics based on the student’s perception such as : patient, distinct, wide perspective, charming, dicipline, encourage student to try to do the best, use grammatical in speaking English, variety of elicitation and explanation, giving explanation of English grammatical, and use English language in communication. The characteristics possessed one of them were : responsible, authority, humorous, attentive to student’s problem, very clear in teaching material, fair, giving, verbal model to use their own communication, respecful, giving example how to use the new vocabulary, giving conclusions about the material, and questioning